Developing a new endograft for the treatment of juxtarenal aortic aneurysms: definition and experimentation (Clinics, 2015)
OBJECTIVES: To analyze angiotomographic parameters of juxtarenal aneurysms to assess the applicability of an endograft model to patients and to create in vitro and in vivo models to assess the new endograft. METHODS: A total of 49 patients with juxtarenal aneurysms were submitted to angiotomographic evaluation, and parameters such as the aortic diameter, the length of the neck, and the angulations of the celiac trunk, superior mesenteric artery and renal arteries; the distances between them; and anatomic variations were analyzed. Based on these parameters, an endograft model was developed and tested in a newly created in vitro model of juxtarenal aneurysm. An experimental model of juxtarenal aneurysm was then established in six pigs weighing 50-60 kg to assess the new endograft model. RESULTS: The angiotomographic parameters of juxtarenal aneurysm measured in this study were similar to those reported in the literature and allowed the development of an endograft based on the hourglass concept, which was applicable to 85.8% of the patients. The in vitro model of juxtarenal aneurysm evidenced good radiopacity and functionality and permitted adjustments in the new device and technical improvements in the procedures for treating these aneurysms. In addition, the porcine model of juxtarenal aneurysm was successfully created in all six animals using a bovine pericardial patch, and use of the new endograft in three pilot procedures evidenced its feasibility. CONCLUSIONS: The Hourglass endograft was rendered applicable to treatment of the majority of patients with juxtarenal aneurysms simply by changing its diameter. Moreover, the new in vitro and in vivo models were shown to be effective for assessing both the presented endograft and experiments assessing the endovascular treatment of juxtarenal aneurysms.